1990
DOI: 10.1095/biolreprod43.5.788
|View full text |Cite
|
Sign up to set email alerts
|

Sodium/Potassium Adenosine Triphosphatase α- and β-Subunit and a-Subunit mRNA Levels during Mouse Embryo Development in Vitro1

Abstract: Changes in sodium/potassium adenosine triphosphatase (Na+/K+ ATPase) and Na+/K+ ATPase mRNA content during preimplantation mouse embryo development were determined. Western blotting, using polyclonal antiserum against guinea pig Na+/K+ ATPase, was used to detect changes in Na+/K+ ATPase alpha- and beta-subunit content during mouse embryo development. Total RNA from mouse embryos was analyzed using Northern and slot blots hybridized with random-primer-labeled cDNA for Na+/K+ ATPase alpha-subunit from sheep kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…mRNAs encoding the beta 1 -isoform were first detected at the bovine morula stage and also in blastocysts (71). Detection of beta 1-subunit mRNAs at the morula stage of bovine development agrees with the increase in the level of beta 1-subunit mRNA (66), beta 1 subunit protein (178), and enzyme activity (61) observed during murine preimplantation development. The absence of beta 1 -subunit mRNAs in earlier bovine stages is distinct from that observed in the mouse and raises the possibility that other beta-subunit isoforms are responsible for the "house keeping" function of the enzyme in these stages.…”
Section: Isoform Expression In the Cow Embryosupporting
confidence: 75%
See 2 more Smart Citations
“…mRNAs encoding the beta 1 -isoform were first detected at the bovine morula stage and also in blastocysts (71). Detection of beta 1-subunit mRNAs at the morula stage of bovine development agrees with the increase in the level of beta 1-subunit mRNA (66), beta 1 subunit protein (178), and enzyme activity (61) observed during murine preimplantation development. The absence of beta 1 -subunit mRNAs in earlier bovine stages is distinct from that observed in the mouse and raises the possibility that other beta-subunit isoforms are responsible for the "house keeping" function of the enzyme in these stages.…”
Section: Isoform Expression In the Cow Embryosupporting
confidence: 75%
“…Beta 1-subunit isoform mRNAs became detectable once again in morulae and underwent a further increase in abundance by the blastocyst stage (66). At first these results appeared to be at variance with the findings of Gardiner et al, (178) who reported the presence of the beta-subunit protein throughout preimplantation development by the technique of immunoblotting. Once again, the differences in sensitivity of methods used for these early studies proved to be the source of this apparent disparity.…”
Section: Isoform Expression In the Mouse Embryosupporting
confidence: 44%
See 1 more Smart Citation
“…The requirement for polarized expression and activity of the Na/K-ATPase in the trophectoderm has been demonstrated in studies examining cavitation and blastocyst re-expansion in the presence of the Na þ -pump specific inhibitor, ouabain (Powers and Tupper, 1975;DiZio and Tasca, 1977;Powers and Tupper, 1977;Biggers et al, 1978;Wiley, 1984;van Winkle and Campione, 1991;Betts et al, 1997;Baltz et al, 1997), or following disruption of trophectoderm cell polarity with blocking antisera against the cell -cell adhesion molecule E-cadherin (Watson et al, 1990a). Increases in Na/K-ATPase activity occur concurrently with the onset of cavitation Tupper, 1975, 1977;Dumoulin et al, 1993;Betts et al, 1998) and are associated with increases in Na þ -pump subunit mRNA (Gardiner et al, 1990;Watson et al, 1990b;Betts et al, 1997) and protein expression (Benos, 1981;Watson and Kidder, 1988;Overstrom et al, 1989;Gardiner et al, 1990). Multiple isoforms of a-and b-subunits (as many as six isozymes) are expressed by murine (Watson and Kidder, 1988;Betts et al, 1997Betts et al, , 1998Jones et al, 1997;Waelchli et al, 1997;MacPhee et al, 2000;Barcroft et al, 2002;Jones et al, 2001 reviewed by Watson and Barcroft, 2001;Kidder, 2002) and bovine (Betts et al, 1997(Betts et al, , 1998 preimplantation embryos.…”
Section: Introductionmentioning
confidence: 97%
“…Research investigating the mechanisms directing blastocyst formation has demonstrated that (a) the Na/K-ATPase assumes a polarized distribution confined to the trophectoderm basolateral membrane regions just before the onset of cavitation (1,2), (b) expression of Na/K-ATPase subunit genes are up-regulated during the morula to blastocyst transition (3)(4)(5)(6)(7), (c) that Na/K-ATPase activity is significantly increased during the morula to blastocyst transition for a number of mammalian species (2, 8 -10), (d) that treatment with ouabain (a potent and specific inhibitor of the Na/K-ATPase) affects cavitation and blastocyst formation in a number of mammalian species (5,(11)(12)(13)(14)(15), (e) that deletion of the Na/K-ATPase ␣1 subunit gene product is linked to aberrant blastocyst formation in vitro and likely peri-implantation lethality in vivo (16), and (f) that Na/K-ATPase also regulates the formation and function of trophectoderm tight junctions (17).…”
mentioning
confidence: 99%